2017
DOI: 10.1108/ijebr-04-2017-0136
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurs as parents: the antecedents and consequence of parenting stress

Abstract: Purpose The purpose of this paper is to understand parenting stress of entrepreneurs and to attempt to extend the empirical evidence on the predictors and consequences of parenting stress for entrepreneurs. Design/methodology/approach This study draws on data from the Household, Income and Labour Dynamics in Australia Survey. The quantitative research method was used. Drawing on the data of 2,051 entrepreneurs, a model was tested using structural equation modeling. Findings The results reveal that social s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 72 publications
1
8
0
Order By: Relevance
“…In addition, scholars have begun exploring external events other than work that act as a stressor, such as parenting demands (e.g. Semerci and Volery, 2018). Recent research has also shown that certain pathological neurodiversity, traditionally regarded as a hindrance (Wiklund et al , 2018), is interpreted or coped with differently by entrepreneurs (Moore et al , 2021), which raises questions about the way these entrepreneurs are appraising their cognitive stressors.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, scholars have begun exploring external events other than work that act as a stressor, such as parenting demands (e.g. Semerci and Volery, 2018). Recent research has also shown that certain pathological neurodiversity, traditionally regarded as a hindrance (Wiklund et al , 2018), is interpreted or coped with differently by entrepreneurs (Moore et al , 2021), which raises questions about the way these entrepreneurs are appraising their cognitive stressors.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors suggest that there is a direct effect between parenting stress and family to work interference; in addition, parenting stress partially mediates the relationship between social support and family to work interference (Boz Semerci & Volery, ). But other authors propose that these multiple roles linked to parenting produce increases in energy through human activity (Correll, Benard & Paik, ; Correll, Kelly, O'Connor & Williams, ), which provides additional personal resources to deal with the stress of life (Marks, ; Parker, Cotton, Yates, Baxter & Arend, ).…”
Section: Introductionmentioning
confidence: 99%
“…Despite these stereotypical beliefs about entrepreneurs, entrepreneurship is often portrayed as an empowering career, associated with high autonomy, an opportunity to work flexible hours, and even the possibility to work without a fixed physical location (Boz Semerci and Volery 2017). Although many entrepreneurs perceive the expected long work hours as a significant job stressor (Boyd and Gumpert 1983), entrepreneurship is seen as a career for women to strike a balance between independent economic activity and fulfilling caring and family obligations.…”
Section: Female Entrepreneurshipmentioning
confidence: 99%
“…The notion that entrepreneurship facilitates work-life integration has received mixed evidence, with some suggesting that the flexibility of entrepreneurial work decreases parenting stress, and others suggesting that the stressors associated with running a business will add to levels of stress rather than diminish them. For an overview, see (Boz Semerci and Volery 2017).…”
Section: Female Entrepreneurshipmentioning
confidence: 99%